2023
DOI: 10.3390/biology12020326
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Mass, Physical Activity, and Dietary Intake during the COVID-19 Pandemic Lockdowns in Canadian University Students

Abstract: This study examined changes in body mass and body mass index (BMI), physical activity, and dietary intake in Canadian university students during the first year of the COVID-19 pandemic. Two self-reported recall surveys were conducted: after the first lockdown in September 2020 (T1) and following the second lockdown in March 2021 (T2). Eligible participants were full-time undergraduate students attending a Canadian university and residing in Canada during the first year of the pandemic. At T1, 510 students (99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This is in agreement to a study in Bangladesh and Canada that also assessed the nutritional status by self-reported measurement in the Covid-19 Pandemic. 16,17 Furthermore, The result showed that most of the students had moderate physical activity for at least 10 minutes each day. This same result was found in a study by Lesmana et al 18 , which mentioned that most of their subjects (university students) had moderate physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…This is in agreement to a study in Bangladesh and Canada that also assessed the nutritional status by self-reported measurement in the Covid-19 Pandemic. 16,17 Furthermore, The result showed that most of the students had moderate physical activity for at least 10 minutes each day. This same result was found in a study by Lesmana et al 18 , which mentioned that most of their subjects (university students) had moderate physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Increased food intake and decreased physical activity explain most of cases of obesity. Furthermore, other factors including genetics, medical conditions, sleep disturbances, and the use of a few medications may predispose individuals to weight gain [81,82]. Diet changes (low-calorie foods rich in fiber, such as fruits and vegetables) and physical activity (150 to 250 min of moderate to intense physical activity per week) represent the first step in obesity control and are good options to be included in a health-oriented routine [25].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diet and physical activity during the COVID-19 pandemic have had an impact on the body weight of students, with a substantial proportion experiencing weight gain. The increase in body weight was more pronounced among students with overweight [ 29 ].…”
Section: Introductionmentioning
confidence: 99%